Performance Analysis of Multiple High Altitude Platform Stations Cellular Network Coverage - Lee, Jaeyeol; Kim, Tae Yoon; Kim, Jae Hyun (International Conference on ICT Convergence, 2023)
The High Altitude Platform Station (HAPS) provides communication services within the stratosphere at an altitude ranging between 20 - 50 km. Utilizing the stable atmospheric conditions of the stratosphere, HAPS offers communication services over extensive areas while facilitating effective communication in line-of-sight (LoS) environments. This paper focuses on the analysis of HAPS cell coverage in a 3GPP standard based cellular communication network where multiple HAPS served as base stations based on the signal-to-interference-plus-noise ratio (SINR). Specifically, the study concentrates on whether user equipment (UE) positioned at the cell edge of the central HAPS maintains a downlink (DL) SINR above a certain threshold. Simulation results show that multiple HAPS 7-cell scenario coverage is achieved at 400 km2 and multiple HAPS one-cell scenario coverage is achieved at 230 km2
Keywords: Atmospheric conditions; Cellular network; Communication service; Effective communication; High altitude platform station; Line of Sight; Lines-of-sight; Network coverage; Performances analysis; Signalto-interference-plus-noise ratios (SINR); HAPS; SINR